Do Inattention/Hyperactivity and Motor Timing Predict Children's Virtual Road-Crossing Performance?. (17th August 2021) - Parr, Morgan N D; Tang, Hanxi; Mallaro, Sophia R; Kearney, Joseph K; Plumert, Jodie M
Abstract: Objective: The goal of this investigation was to examine how individual variation in inattention and hyperactivity is related to motor timing difficulties and whether children's performance on simple laboratory timing tasks is related to their performance on a virtual road-crossing task using a head-mounted virtual reality display system. Methods: Participants were a community sample of 92 9- to 11-year-old children. Parents completed questionnaires assessing their child's inattention and hyperactivity. Children completed two simple motor timing tasks (duration discrimination and synchronization-continuation) and crossed roads with continuous traffic in a head-mounted VR system. Results: Higher parent-reported inattention and hyperactivity predicted poorer performance in the duration discrimination and synchronization-continuation tasks, but not the virtual pedestrian road-crossing task. Children with higher tap onset asynchrony in the synchronization-continuation task had poorer timing of entry into the gap in the virtual pedestrian road-crossing task. Conclusions: The findings provide further evidence that timing deficits are associated with individual differences in inattention and hyperactivity and that timing difficulties may be a risk factor for functional difficulties in everyday life.